Evaluating the Efficiency of Lettuce Disinfection According to the Official Protocol in Iran - M Yarahmadi; M Yunesian; MR Pourmand; A Shahsavani; I Mubedi; B Nomanpour; K Naddafi (Tehran University of Medical Sciences, 2012)
Background: The objective of this study was to evaluate the efficacy of Sanitization of Lettuce according to the protocols set forth by Iranian Ministry of Health and Medical Education for reducing populations of total coliform, fecal coliform, and helminth eggs present on lettuce. Methods: In the present study, we determined the load of total coliform, fecal coliform, and parasites of lettuce. The lettuce was sanitized by protocol of Iranian Ministry of Health and Medical Education. The protocol consists of 3 levels to disinfect the fruits and vegetables. The procedure was as follows: first washing stage. The leaves of leafy vegetables washed with tap water, second stage, separation of helminth eggs by 3 to 5 droplets of detergent per liter for 5 min; third stage, disinfection of vegetables by calcium hypochlorite solution (with 200 mg/l free chlorine) for 5 min; and finally  the disinfected vegetables were washed  with tap water. Results: The average initial levels of total coliform and fecal coliform in the samples were 3.36 log10 cfu/g and 2.31 log10 cfu/g, respectively. Helminth eggs were not detected in any of the samples tested. The efficiency of total coliform and fecal coliform removal were 78.1% (0.75 log10cfu/g) and 79.6% (0.67 log10cfu/g), respectively, after washing. This increased up to 94.8(1.44 log10cfu/g) and 98.5% (1.90 log10cfu/g) after the use of detergent. Chlorine disinfection rose these amounts up to 98.3% (2.18 log10cfu/g) and 100% (2.31 log10cfu/g), respectively. Conclusion: By applying the protocol large parts of microorganisms existing on lettuce have indeed been removed.